Deep Eutectic Solvents: Fundamental Aspect, Characterizations and Applications - Dangre, Pankaj V.; Borase, Harshada P.; Gunde, Mahendra C.; Pethe, Anil M.; Borkar, Maheshkumar R. (Recent Advances in Drug Delivery and Formulation, 2023)
Deep eutectic solvents (DESs) containing bioactive have been explored as potential choices for therapeutic efficiency enhancement. DESs are regarded as superior compared to established solvents owing to accessibility, storage conditions, synthesis, and low cost. As such, intensive research has taken place in different disciplines, especially nutraceuticals, foods and pharmaceuticals. The applications of DESs, especially in nutraceuticals and pharmaceutical delivery, have shown great promise. Despite these different successes, the safety issues of these DESs need to be properly identified. A safe mixture of DESs must be developed to take its broad range of advantages to the nutraceutical industry, and, therefore, its nutraceutical applications can only be introduced if DESs are known to have profiles of negligible or minimal toxicity. This review emphasizes the fundamental aspects needed to have a better understanding of DESs. It covers the current prospects of DES, including types, properties, formulation components and characterization methods. The several characterization methods, viz., pH, density, refractive index, viscosity, surface tension, solubility, polarized optical microscopy, x-ray diffraction studies, Fourier transforms infrared spectroscopy, and nuclear magnetic resonance spectroscopy are also mentioned. Further, the promising applications of DESs in different nutraceutical and pharmaceutical domains are highlighted.
Keywords: nutraceuticals